On homogenization of solutions of the poisson equation in a perforated domain with different types of boundary conditions on different cavities - Jäger, Willi; Olejnik, Olʹga A.; Shaposhnikova, Tat'yana Ardolionovna (Applicable analysis, 1997)
In this paper we consider boundary value problems in perforated domains with periodic structures and cavities of different scales, with the Neumann condition on some of them and mixed boundary conditions on others. We take a case when cavities with mixed boundary conditions have so called critical size (see [1]) and cavities with the Neumann conditions have the scale of the cell. In the same way other cases can be studied, when we have the Neumann and the Dirichlet boundary conditions or the Dirichlet condition and the mixed boundary condition on the boundary of cavities.There is a large literature where homogenization problems in perforated domains were studied [2];-[7];
Published online: 02 May 2007
Gesehen am 30.08.2018